HUBUNGAN INDEKS MASA TUBUH DENGAN KEJADIAN ANEMIA - Muslimah, Thatik; Zein, Asmar Yetti; Maryani, Tri (Poltekkes Kemenkes Yogyakarta, 2014)
Background: Based on Household Health Survey data (2004) the prevalence of anemia in teenagers in age 10-18 years is 57.1%. Teenagers is prone to get anemia because teenagers who are growing, starting to menstruate, and starting to think about the ideal body shape, thus causing a change in diet that affects the body mass index. Objective: Knowing the relationship between body mass index with Anemia incident. This research uses a survey method with cross sectional analytic. The study is conducted in SMA N 3 Bantul on 14-15 May 2013. Samples were taken by purposive sampling techniques as many as 83 respondents. This research instrument is the adult weight scales, mikrotoa, and Portable Digital Hemoglobin Analyzer EASY TOUCH GCHb, that is analyzed using Chi Square. Results: The prevalence of anemia in class XI student was 42.2%. Body Mass Index mostly within the normal ranges, 83.1%. Analysis with Chi Square test results are known p-value 0.002 (<0.05) and RP of 2.26 (CI 1.479 to 3.450). Conclusions: The relationship between body mass index with incidence of anemia. It means that Body Mass Index has the higher risk of anemia compared to body mass index that is not at risk